Mobile Cloud Computing Applications survey: Security and Privacy - Kumar Rahul; Rohitash Kumar Banyal (AG Volumes, 2022)
Mobile cloud computing, a novel approach for mobile computing that has been in development for decades, results from the combination of powerful mobile devices and cloud computing services. TheMCC enables cloud computing to be integrated into the mobile environment and solves performance issues. As a result, The Cloud Technology is able to transcend the limits of mobile computing. For mobile apps, cloud technology offers adequate computational capacity to operate on a cloud platform. By offloading applications to a resource-rich Remote server, the novel technology known as mobile cloud computing (MCC) is introduced to overcome the limitations of mobile devices (such as battery life, storage capacity, processing capacity). MCC integrates two technologies (Mobile Computing, Cloud Computing). MCC is described in this study, as well as security and privacy issues, threats, and obstacles that are associated with MCC.